2012
DOI: 10.1080/19440049.2012.672340
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between environmental factors, dry matter loss and mycotoxin levels in stored wheat and maize infected withFusariumspecies

Abstract: This study examined the relationship between storage environmental factors (water activity (a(w)) (0.89-0.97) and temperature (15°C-30°C)), colonisation of wheat and maize by Fusarium graminearum and F. verticillioides respectively and the dry matter losses (DMLs) caused and quantified by contamination with deoxynivalenol (DON), zearalenone (ZEA) and fumonisins (FUMs) during storage. Fungal growth was assessed by the amount of CO(2) produced under different interacting conditions of a(w) and temperature. DMLs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 27 publications
4
35
0
1
Order By: Relevance
“…F. graminearum becomes well established on grain at 28°C (Mylona et al 2012). The rate of ZEN production varies depending on the incubation conditions, and the highest production is obtained with cultures transferred to 12°C (Sherwood & Peberdy 1972).…”
Section: Introductionmentioning
confidence: 97%
“…F. graminearum becomes well established on grain at 28°C (Mylona et al 2012). The rate of ZEN production varies depending on the incubation conditions, and the highest production is obtained with cultures transferred to 12°C (Sherwood & Peberdy 1972).…”
Section: Introductionmentioning
confidence: 97%
“…According to Seitz et al, (1982), the contribution to DML from fungi increases during storage at a rate dependent on moisture, temperature, amount and type of kernel damage and level of fungal inoculum on the grain. Recent studies have examined the use of CO2 production during storage of maize, wheat and rice as an indicator of the level of AFs, FMs, deoxynivalenol (DON), ZEA and trichothecenes A (TCT-A) contamination (Garcia-Cela, Kiaitsi, Medina, et al, 2018;Martín Castaño, Medina, & Magan, 2017a,b;Mylona & Magan, 2011;Mylona, Sulyok, & Magan, 2012) These studies proved that it is possible to utilise the progressive increase in the respiration rate under increasingly conducive conditions for mould growth due to the oxidation of carbohydrates and hence CO2 production, water vapour and heat during aerobic respiration to calculate quality losses as DML. DML can be quantified based on CO2 production and respiration rates using Gas Chromatography (GC) and these data sets are used as a "storability risk index" to predict overall quality changes in stored grain.…”
Section: Introductionmentioning
confidence: 99%
“…Seitz et al, (1982) showed that a loss of 0.5% DML in stored maize was enough to downgrade this commodity from food to feed, with associated increased risks of aflatoxin contamination. DML of between 1 and 2% in cereals (rice, wheat, maize) contaminated with Fusarium toxins (FMs, DON and ZEA) resulted in contamination levels which exceeded the EU legislative limits (Garcia-Cela, Kiaitsi, Medina, et al, 2018;Martin Castaño, Medina, & Magan, 2017a,b;Mylona, Sulyok, & Magan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that for F. verticillioides the pattern of FB 1-4 production in maize and the relative amount of FB 1 compared to FB 2 , FB 3 and FB 4 , is related to climatic factors, such as water activity and temperature Mylona et al, 2012). It was also shown that for F. verticillioides the pattern of FB 1-4 production in maize and the relative amount of FB 1 compared to FB 2 , FB 3 and FB 4 , is related to climatic factors, such as water activity and temperature Mylona et al, 2012).…”
mentioning
confidence: 99%